“Mundo da arte” na escola : a identificação de obras de artes visuais por alunas e alunos do ensino fundamental - Severo, Márjorie Garrido (2017)
What do students of the elementary school identify as work of art? By trying to answer this question I actually aim to understand the relation between the identification of art of graduating students of elementary schools and the images commonly used by their teachers in class. The problem of the identification of what is a work of art was debated by the philosopher Danto in his thesis about the world of art. On it he argues that the problem is part of a deeper discussion, and is related to the difficulty of discerning a work of art from a common object in the way it presents itself to him in the contemporaneity. My goal is to show that the approach used by teachers in class is the main reference to students to identify what is art. I approach the presence or the lack of work of art and its reproductions in the formal education in the Brazilian historical process and the emergence of the thematic of contemporary art. This is done with the precise objective of giving a historical dimension to the problem.The methodology is the mixed methods reuniting the content analysis of Bardin, the knowledge inventory of Charlot, photo-elicitation aspects of Harper, the studies of investigation based on the visual arts of Viadel, and on the semiotic perspective of Pierce. In the first phase of the research 348 students of the ninth grade of the elementary school from eight public and private schools of metropolitan area of Aracaju took part in the research. Of these, 61 are organized in groups of debate, and 8 art teachers are interviewed. The phase of interpretation is developed through the processes of comparison, quantification, categorization, and interpretation of the data and reports from teachers and students. This phase consists of nucleons of signification: subjective, art practice, and referencial. With these I identify the emphasis of the notion of art manifested by students as expression, painting, and culture, respectively. The result of the application of photo-elicitation is that 74% of reflexes among the images of work of art used by teachers and the identification of art by the students. The results of the present research support the thesis and identify a relation based on context and art practice developed by art teachers at schools.